Hypochondriac Disorder in OSMF Patient - Baba Sankar Sahu1 , Abhishek Ranjan Pati2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The main purpose of this article is to present a review on oral submucous fibrosis patients, those who aresuffering from hypochondriasis disorder and identifying its interrelationship with their family how they arealso suffering due to this problem. The article also focuses on the sign and symptoms of this disorder. Also,it highlights the treatment planning of this disorder